Vulvovaginal Hygiene Practices Among Pregnant Ladies in Rural West Bengal: A Cross sectional Observational Study - Mitra, Partha Sarathi; Ghosh, Nupur; De, Avik; Chatterjee, Monalisa; Khatua, Pamela; Ahmed, Khwaja Alim (Journal of Midwifery, 2024)
Vulvovaginitis is very common in pregnancy in our country. Lactobacilli are the normal vaginal microflora which maintains acidic vaginal pH. Lack of hygiene may lead to colonisation of coliforms resulting in vulvovaginitis which in turn may cause serious health problems for the mother and the new-born. A cross-sectional observational study was conducted on pregnant women attending antenatal OPD of BMCH on every Wednesday between 1st July to 31st December, 2022 with a preformed questionnaire which dealt with different parameters to observe whether present pregnancy was complicated by any vulvovaginal ailments. Although they had little knowledge about vulvovaginal microbiota, pathogenesis and morbidity of vulvovaginitis during pregnancy, most had a practice of vulvovaginal cleaning with plain water and not commercial douching. Protection against vulvovaginal infection is particularly important for pregnant women as it increases the risk serious maternal and neonatal morbidities. Routine washing of the vulva with plain water is beneficial to maintain cleanliness and prevent vulvovaginal infection. Vulvar cleansing products does not treat infections rather disrupts normal vaginal microbiota thus promotes colonization of uropathogens. Prevention of vulvovaginal infection by simple hygiene maintenance can be achieved by educating antenatal mothers during their visits.